Maturation promoting factor destabilization mediates human chorionic gonadotropin induced meiotic resumption in rat oocytes. (16th August 2017) - Tiwari, Meenakshi; Chaube, Shail K.
Abstract : Human chorionic gonadotropin (hCG) mimics the action of luteinizing hormone (LH) and triggers meiotic maturation and ovulation in mammals. The mechanism by which hCG triggers meiotic resumption in mammalian oocytes remains poorly understood. We aimed to find out the impact of hCG surge on morphological changes, adenosine 3′, 5′‐cyclic monophosphate (cAMP), guanosine 3′, 5′‐cyclic monophosphate (cGMP), cell division cycle 25B (Cdc25B), Wee1, early mitotic inhibitor 2 (Emi2), anaphase‐promoting complex/cyclosome (APC/C), meiotic arrest deficient protein 2 (MAD2), phosphorylation status of cyclin‐dependent kinase 1 (Cdk1), its activity and cyclin B1 expression levels during meiotic resumption from diplotene as well as metaphase‐II (M‐II) arrest in cumulus oocyte complexes (COCs). Our data suggest that hCG surge increased cyclic nucleotides level in encircling granulosa cells but decreased their level in oocyte. The reduced intraoocyte cyclic nucleotides level is associated with the decrease of Cdc25B, Thr161 phosphorylated Cdk1 and Emi2 expression levels. On the other hand, hCG surge increased Wee1, Thr14/Tyr15 phosphorylated Cdk1, APC/C as well as MAD2 expression levels. The elevated APC/C activity reduced cyclin B1 level. The changes in phosphorylation status of Cdk1 and reduced cyclin B1 level might have resulted in maturation promoting factor (MPF) destabilization. The destabilized MPF finally triggered resumption of meiosis from diplotene as well as M‐II arrest in rat oocytes. Abstract : hCG surge decreased cyclic nucleotides and Cdc25B expression levels but increased Wee1, Thr14/Tyr15 phosphorylated Cdk1 levels and Cdk1 activity. hCG surge significantly decreased Thr161 phosphorylated Cdk1 level as well as Emi2 levels. The decreased Emi2 expression level was associated with increased APC/C and MAD2 expression levels that reduced cyclin B1 level. The changes in specific phosphorylated status of Cdk1 and reduced cyclin B1 level destabilized MPF. The destabilized MPF finally triggered meiotic resumption from diplotene‐ as well as M‐II arrest in rat oocytes.